Satellite Image Resolution Enhancement based on Dual-Domain Filtering - Rasool Reddy, K; K.NagaPrakash, Dr; K.Prasanthi Jasmime, Dr; Tulasidas, M (International Journal of Engineering and Technology, 2018)
Satellite images place vital role in agriculture, Disaster mitigation and geosciences applications. Satellite images include both spatial and temporal resolution, in that spatial resolution is influence the accuracy of ground objects. The main idea of this work is to enhance the resolution of satellite images. In this work, a dual domain filtering based approach is introduced for resolution enhancement (RE). Initially, the source image is subdivided into approximation and detail coefficients by Stationary Wavelet transform (SWT). The detail coefficients are interpolated based on bi-linear interpolation. The interpolated detail coefficients are applied to Non-Local Means (NLM) filter to minimize the artifacts produced by SWT. The filtered detail and approximation coefficients of source image are fed to ISWT to attain high resolution (HR) image. The proposed system is superior to other existing strategies like DWT-NLM and DWT-SWT.Â